1986
DOI: 10.1001/jama.1986.03380070087025
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Positive-Pressure Ventilation With Extracorporeal CO2 Removal in Severe Acute Respiratory Failure

Abstract: Forty-three patients were entered in an uncontrolled study designed to evaluate extracorporeal membrane lung support in severe acute respiratory failure of parenchymal origin. Most of the metabolic carbon dioxide production was cleared through a low-flow venovenous bypass. To avoid lung injury from conventional mechanical ventilation, the lungs were kept "at rest" (three to five breaths per minute) at a low peak airway pressure of 35 to 45 cm H2O (3.4 to 4.4 kPa). The entry criteria were based on gas exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
102
0
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 581 publications
(107 citation statements)
references
References 17 publications
2
102
0
3
Order By: Relevance
“…The rationale of their advanced technique was to prevent further damage to the diseased lungs by reducing their motion (pulmonary rest) with application of only a few ventilator breaths with low V T and low peak inspiratory pressures. This lung protective mechanical ventilation strategy became known as low-frequency positive-pressure ventilation (LFPPV) [30]. With this method, oxygen uptake and carbon dioxide removal were dissociated.…”
Section: Historymentioning
confidence: 99%
See 3 more Smart Citations
“…The rationale of their advanced technique was to prevent further damage to the diseased lungs by reducing their motion (pulmonary rest) with application of only a few ventilator breaths with low V T and low peak inspiratory pressures. This lung protective mechanical ventilation strategy became known as low-frequency positive-pressure ventilation (LFPPV) [30]. With this method, oxygen uptake and carbon dioxide removal were dissociated.…”
Section: Historymentioning
confidence: 99%
“…The so-called LFPPV-ECCO 2 -R technique was performed at low extracorporeal blood flows (20-30% of cardiac output), so that a venovenous bypass technique instead of an arteriovenous one sufficed, which turned out to be less detrimental to blood cells, coagulation and internal organs. Using LFPPV-ECCO 2 -R, Gattinoni et al [30] reported survival rates of up to 49%. In the following years several centres corroborated the promising survival rates of around 50% and higher (Fig.…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations
“…: ECM021 ^1:^* oji1 brane gas exchange device)2] "-i] "An 4* 514. [6] ^*) iLAfe û oll - §-0)401 ARDSo1)4 IE)) Ü^Et^S 01:7)51 * èl)a:*>AS«l 2)-£*t *4* ûl)«]-4o^ VILI* to)fe 11 …”
mentioning
confidence: 99%